#1**+5 **

3^-2 (a^4)

It's meticulous to solve a negative exponent, so find the reciprocal of 3^-2 and change the -2 to a positive 2.

1 / 3^2

There! Now add the a^4 back...

1(a^4) / 3^2

a^4 / 3^2

First, solve 3^2...

3 * 3 = 9

Put that in...

a^4 / 9

And that's it!

3^-2 * a^4 = a^4 / 9 = 1/9a^4

Anonymous4338 Apr 8, 2016

#1**+5 **

Best Answer

3^-2 (a^4)

It's meticulous to solve a negative exponent, so find the reciprocal of 3^-2 and change the -2 to a positive 2.

1 / 3^2

There! Now add the a^4 back...

1(a^4) / 3^2

a^4 / 3^2

First, solve 3^2...

3 * 3 = 9

Put that in...

a^4 / 9

And that's it!

3^-2 * a^4 = a^4 / 9 = 1/9a^4

Anonymous4338 Apr 8, 2016

#2**+5 **

\({3}^{-2}\times{a}^{4}\)

\(\frac{1}{{3}^{2}}\times{a}^{4}\)

\(\frac{1}{9}\times{a}^{4}\)

\(\frac{1}{9}{a}^{4}\)

\(\frac{{a}^{4}}{9}\)

.gibsonj338 Apr 8, 2016